Opportunities for the Sustainable Development of Rural Areas un Serbia - Cizler, Jasna (Problemy Ekorozwoju, 2013)
This article discusses current problems in rural Serbia and investigates development opportunities. The intention is to indicate strengths and weaknesses of the present situation and to highlight possible solutions for sustainable development. The results were presented in the form of potential methods for future development and are discussed through several issues: sustainable regional development and sustainable rural development as an alternative to excessive urbanization; cultivating the tradition of the village and development of rural tourism; cultural heritage in the service of sustainable development; building the ecological image of the village through promotion of the local economy and organic farming; and social capital and infrastructure development as factors of sustainable development. The conclusion is that in planning the development of rural areas, villages should be seen as a value and their potentials and regional characteristics should be promoted and used in order to contribute to sustainable development.